THE EFFECTIVENESS OF RED BETEL LEAVES ON HEALING PERINEAL WOUNDS AT THE KENANGAN HEALTH CENTER DELISERDANG REGENCY YEAR 2022 - Simanjuntak, Mastari; Debora Sophia Laoren Sitompul; Rumondang Sitorus; Asnita Sinaga; Esra Agustina Gultom (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
The use of betel leaves can accelerate the healing of perimium wounds, there is a significant difference in the healing time of perimetry wounds between the experimental and control groups. Based on these results, it can be said that the use of betel leaves is effective in accelerating the healing of periamium wounds. The effectiveness of red betel leaf in the treatment of perineal wounds can be concluded that the average healing time of perineal wounds using red betel leaf infusion is 3-4 days, while the average healing time using iodine is 5-6 days. This means that the treatment of perineal wounds in postpartum mothers is more effective using red betel infusion than iodine. This type of research is a Quasi experiment (pseudo-experiment) research using a quantitative approach that aims to explain, test the relationship between variables and to find the effectiveness of red betel leaf on the healing of perineal wounds. The research design that the author will use in this study is a Pretest-posttest design using two research groups (One Group Pretest-posttest Design). The development is by means of one measurement in front (pretest) before the treatment and after that another measurement is carried out (post-test). The initial measurement provides a pre-test using the observation method to see directly how wide the birth canal wound is. It is known that of the 19 respondents, the majority of respondents are in the age group of 19 years - 30 years, namely as many as 17 respondents (89.5%) and 2 respondents (10.5%) in the age group of 31 years - 45 years.